Functional Outcome Of Posteromedial Soft Tissue Release Following Failed Ponseti Technique In Children With Congenital Talipes Equinovarus - Gumaste, Abhishek; B Naik, Rajesh (Journal of Neonatal Surgery, 2025)
Background: The complicated deformity known as idiopathic congenital talipes equinovarus is challenging to treat. Although the majority of orthopaedicians agree that non-surgical treatment (Ponseti method) should be used as a first line of treatment, if non-surgical treatment is unsuccessful, surgical soft tissue release should be recommended for improved outcomes. The purpose of the study was to evaluate the effectiveness of the treatment method by conducting follow-up on 15 patients who undergoes posteromedial soft tissue release. Methods: Posteromedial soft tissue release (PMSTR) was performed on 15 patients at KLE Jagadguru Gangadhar Mahaswamigalu Moorsavirmath Medical College and Hospital, Department of Orthopaedics between June 2023 and May 2024. Up to a year and a half, patients received routine follow-up care. The Denis-Brown classification was used to grade the severity of foot abnormalities. Results: The study included 15 patients, 93% patients aged less than 4 years, with male predominance 60%. 40% were bilateral cases. The average duration of casting done was 8.2 ± 1.4 weeks. Pre operative Pirani scoring showed significant deformity with mean of 5.2 ± 0.4, and postoperatively it was improved to 1.1 ± 0.6. Functional outcome measured by modified Laaveg and Ponseti score revealed 60% of patient had excellent results. Conclusion: The PMSTR technique significantly reduces the need for extensive corrective surgery and is a safe and economical treatment for congenital idiopathic clubfoot after failed Ponseti method. Technique failure can be attributed to late-life surgery and noncompliance with orthotics following surgery.